Brief review on the limit state function of dynamic scour protections - Tiago Ferradosa (2019)
Abstract Offshore foundations, namely for offshore wind, wave and tidal applications, often require the use of scour protections. Rip-rap scour protections are an important element of the foundation to ensure that the natural frequency stays within the design limits. Scour protection design still presents a remarkable empirical nature, which typically leads to uncertainty on their behaviour under extreme met-ocean conditions. Therefore, reliability assessment of scour protections has been seen as a possibility to account for design uncertainty and to optimise the scour protections. However, the definition of a suitable limit state function is still a matter of research focus, namely, regarding the proper definition of the acceptable damage level for dynamic scour protections. This research provides a brief review on the recent studies related to both the limit state function and the calculation of damage numbers through bathymetric data. A discussion is raised on how the methodologies for calculating the damage number may influence the limit state function and a theoretical example is given to assess the effects on the probability of failure. Results have shown that the acceptable damage number requires a clearer definition, which should be based on the number of layers of rock material and the area of filter exposure. In addition, this research highlights the need for alternative ways to assess damage.